Miscibility and crystallinity of poly(3-hydroxybutyrate)/poly(3-hydroxybutyrate-co-3-hydroxyvalerate) blends - Conti D.S. (2006)
With the objective of developing new biodegradable materials, the miscibility and the crystallinity of blends of poly(3-hydroxybutyrate), P(3HB), and poly(3-hydroxybutyrate-co-3-hydroxyvalerate), P(3HB-co-3HV), have been studied. P(3HB) (300 kg mol-1)/P(3HB-co-3HV)-10% 3HV (340 kg mol-1) blends were prepared by casting in a wide range of proportions, and characterized by differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FT-IR). The experimental values for the glass transition temperatures (Tg) are in good agreement with the values provided by the Fox equation, showing that the blends are miscible. It was observed that the Tg and the melting temperature (Tm) decreases with the increase in the P(3HB-co-3HV)-10% 3HV content, while the crystallization temperature (Tc) increases. FT-IR analyses confirmed the decrease on the crystallinity of P(3HB)/P(3HB-co-3HV)-10% 3HV blends with higher copolymer contents. Bands related to the crystallinity were changed, due to the copolymer content that produced miscible and less crystalline blends. © 2006 Elsevier B.V. All rights reserved.